(untitled) (Journal of Pathology of Nepal, 2023)
Background: Skin adnexal tumors are a spectrum of benign and malignant tumors that differentiate toward or arise from the adnexal unit of the skin. These rare tumors pose a challenge in diagnosis, and often, a discrepancy is seen between clinical and histopathological diagnosis. Materials and methods: This single institutional study was carried out among 36 patients who presented with swelling. An initial diagnosis was considered based on the clinical history followed by histopathological examination. Results: Among the 36 patients, only 4 had malignant tumors. Among them, 3 had sebaceous differentiation, and 1 had apocrine and eccrine differentiation. Among the benign, 14 had follicular differentiation, 12 had apocrine and eccrine differentiation, and 6 had sebaceous differentiation. The clinic-pathological correlation was 65%. Conclusions: An accurate diagnosis is not possible with just the clinical features. Histopathologic examination is considered the gold standard for diagnosis and categorization.